Ethnocentrism as a moderator on the relationship between celebrity's source credibility and the purchase intention of cosmetic products among Malaysians - Fatima Zohra Chekima (2019)
Globalization has led to an increased competition as firms expand their coverage including various domestic and international markets. One of the industries that has been influenced by the globalization is the cosmetic industry. This industry has been growing and expanding around the world in both developed and developing countries. As a result, customers have a growing selection of purchase options, including an increasing proportion of foreign products and brands. It is clear that there is a need for better understanding of the factors that determine the choice of consumers of domestic and foreign products in different market settings. One of the strategies that are used by companies to differentiate their cosmetic products is through celebrity endorsement. Other than that, another important factor that affects consumers' purchase intention is the consumer ethnocentrism level. Consumers in different countries have different preference over local and international celebrity. Thus, the objective of this research is to propose a suitable approach and develop a conceptual framework to examine the factors influencing the purchase intention of cosmetic products. The study has used the Partial Least Square statistical analysis to test the model developed through an empirical sample size of 189 respondents. The results have shown that attractiveness, expertise and trustworthiness of the celebrity endorser had significant positive relationship on the cosmetic product purchase intention. Moreover, the moderating role of consumer ethnocentrism between the attractiveness, expertise and trustworthiness and cosmetic product purchase intention were analyzed. Based on the results obtained, the attractiveness, expertise and trustworthiness of a celebrity endorser would be able to increase the purchase intention of the endorsed product. The outcome of the study also indicated that when the ethnocentrism of consumer is higher, the attractiveness and trustworthiness are stronger. The finding of this study could help cosmetic products marketers to design more suitable ads in terms of celebrity characteristics and understand the role of consumer ethnocentrism in the consumer's decision making. Local and international companies interested in expanding their cosmetic products market in Malaysia could consider the findings of this study while drafting a more effective strategy to better market their products and to encourage higher cosmetic products purchase intention. Therefore, companies would be able stand out of the chaos by using endorser which is more suitable to reach the consumers in Malaysia.